The Effect of Direct Current Stimulation versus T‐Wave Shock on Defibrillation Threshold Testing. Issue 10 (26th July 2015) - ITO, HIROYUKI; KAWAMURA, MITSUHARU; BADHWAR, NITISH; VEDANTHAM, VASANTH; TSENG, ZIAN H.; LEE, BYRON K.; LEE, RANDALL J.; MARCUS, GREGORY M.; GERSTENFELD, EDWARD P.; SCHEINMAN, MELVIN M.
<x xml:space="preserve">Abstract</x> Introduction There are several methods to induce ventricular fibrillation (VF) during defibrillation threshold (DFT) testing. Delivering a shock at a critical time during the T wave (T‐shock) is the conventional approach, while delivering a constant direct current voltage (DC stim) from the implantable cardioverter defibrillator is an alternative method. Only a few reports compare VF induction methods. The purpose of this study was to evaluate the effects and safety of DC stim versus T‐shock. Methods We retrospectively investigated 414 consecutive patients undergoing DFT testing. We compared the two groups (DC stim and T‐shock) with respect to clinical characteristics, electrocardiogram (ECG) changes, and complications. Results Ventricular arrhythmia, including ventricular tachycardia (VT) and VF, was induced by DC stim in 93 patients or T‐shock in 321 patients. No more than three attempts were performed during one procedure. There was no significant difference in the baseline ECG, induced tachycardia cycle length (TCL), or complications between the two groups. However, the induced TCL was significantly shorter than the clinical TCL regardless of induction method (P = 0.001). Five patients suffered major complications (i.e., electromechanical dissociation or incessant VT). A history of atrial fibrillation was significantly greater in patients with major complications than the others (80% vs 24%, P = 0.004), and was an independent predictor on multivariate analysis. Conclusions There is no significant difference in induced TCL or complications between the DC stim and T‐shock. The induced TCL is significantly shorter than clinical TCL regardless of induction method.